2021
DOI: 10.2147/ijgm.s300257
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Subclinical Deterioration of Right Ventricular Function by Three-Dimensional Speckle Tracking Echocardiography in Breast Cancer Patients Undergoing Anthracycline-Based Chemotherapy

Abstract: Objective: This study was aimed at assessing the longitudinal strain changes of RV function using three-dimensional speckle tracking echocardiography (3D STE) in breast cancer patients receiving anthracycline chemotherapy. Patients and Methods: A total of 95 women with breast cancer receiving epirubicin (360 mg/m 2) underwent 3D STE at baseline, the end of chemotherapy and 12 months after chemotherapy. 3D STE assessment included RV ejection fraction (EF), LV global longitudinal strain (GLS), RV GLS, and RV fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Unlike ours, their study did not detect any signi cant reduction in LVEF after six months of follow-up and concluded that doxorubicin therapy is associated with subclinical RV dysfunction. [28] The study of Xu et al [34] who assessed RV function in 95 women with breast cancer receiving epirubicin therapy, found that 3D GLS of LV and both RV GLS and FWLS were depressed signi cantly at 12 months without the occurrence of cardiotoxic affection of LVEF and RVEF, these variations of 3DRV strain allow the identi cation of subclinical RV dysfunction when conventional parameters unaffected, same as our results.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Unlike ours, their study did not detect any signi cant reduction in LVEF after six months of follow-up and concluded that doxorubicin therapy is associated with subclinical RV dysfunction. [28] The study of Xu et al [34] who assessed RV function in 95 women with breast cancer receiving epirubicin therapy, found that 3D GLS of LV and both RV GLS and FWLS were depressed signi cantly at 12 months without the occurrence of cardiotoxic affection of LVEF and RVEF, these variations of 3DRV strain allow the identi cation of subclinical RV dysfunction when conventional parameters unaffected, same as our results.…”
Section: Discussionsupporting
confidence: 82%
“…Cherata et al [32] who assessed RV systolic function in 68 cancer patients receiving cardiotoxic agents demonstrated that a 17% reduction of RV FWLS had a sensitivity of 55% and a speci city of 70% with an AUC of 0.75 to identify patients with CTRCD Another study reported that the optimal cut-off value of 17.5% of 3D RV FWLS percent changes showed high prognostic accuracy for subclinical cardiac dysfunction, with an AUC of 0.74, a sensitivity of 80.5%, and a speci city of 65.8%. [34] Our study found that the longitudinal strain analysis permits early identi cation of subclinical RV dysfunction when the standard 2D indices of RV function are unaltered. RV FWLS is more accurate than RV GLS in the evaluation of RV systolic function since the intraventricular septum is a constituent part of the LV.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Other authors have also described similar results since they have demonstrated the lack of association between an alteration in cardiac function and treatment with vincristine ( Maraldo et al, 2015 ). This could suggest the existence of subclinical cardiotoxicity after treatment with this antitumor, in the same way that occurs with other chemotherapeutic drugs such as cisplatin or doxorubicin ( Demkow et al, 2011 ; Sandamali et al, 2020 ; Xu et al, 2021 ). It should be noted that, in our study, after chronic treatment with vincristine, we observed a slight, although not significant, elevation in the coronary perfusion pressure that was maintained even after the suspension of treatment.…”
Section: Discussionmentioning
confidence: 88%
“…Two hundred and fifty-nine studies were identified from databases and manual search after excluding duplicated studies. Finally, twenty-one trials published between 2013 to 2021, including 1,355 participants, were adopted in our analysis ( 17 - 37 ). The detailed process of literature searching and the explanation for exclusion are described in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%